Pengaruh Suhu Dan Tekanan Vulkanisasi Terhadap Morfologi Dan Sifat Karet Alam Vulkanisat (Thermoset Rubber) Dengan Filler Abu Sawit / Carbon Black - Muhammad Isra; Irdoni Irdoni; Bahruddin Bahruddin (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
The production of natural rubber increase sufficient good in indonesia, while the natural rubber to be a product with a high valuable price still less developed than other countries. Therefore,we have to eforts it to employing this natural rubber be a product with a high valuable price from the raw material (natural rubber) to be vulcanized natural rubber using vulcanization process. The purpose of this study is to obtain the best conditions of the vulcanization process in the manufacture of vulcanized natural rubber with fly ash/carbon black filler, which is the variation of temperature 140, 150 and 160 °C and preasure of 50,100,150 and 200 kgf/cm2. The results vulcanized natural rubber of will be tested, it’s mecanical properties and morphology. Based on average yield mecanical properties and morphology tested is obtained that the operating conditions vulcanization process is temperature 150 °C and a pressure of 200 kgf/cm2.     Keyword : Natural rubber, Vulcanization, Vulcanized Natural Rubber.